Manajemen Pengendalian Logistik Berbasis Sistem Informasi Gudang (Universitas Negeri Semarang, 2022)
The purpose of this study is to determine the process of handling logistics control management based on warehouse information systems in Building H, State University of Semarang. This qualitative descriptive study used 10 informants consisting of 5 related informants, 2 involved informants, and 3 principal informants. Data collection techniques in this study used observation, interviews, and documentation techniques. Data analysis used data reduction, data presentation, and drawing conclusions. The results showed that logistics control was controlled by an online-based Asset and Warehouse Information System (SiAgung) and an offline-based SIMAK BMN. The problem with the system used is that the online system is still under development, so sometimes the control of the demand for goods is wrong, while the offline system continues to be updated continuously from the center. In addition to the system, unorganized warehouse arrangements, unavailability of reports on the use of goods per unit, and the absence of SOPs (Standard Operating Procedures) for logistics arrangements in warehouses are also obstacles to the logistics control management process.